Postcolonial amazons : female masculinity and courage in ancient Greek and Sanskrit literature - Penrose, Walter Duvall Jr. (Oxford University Press, 2016)
Scholars have long been divided over whether the Amazons of Greek legend actually existed. 'Postcolonial Amazons' offers a ground-breaking re-evaluation of the place of martial women in antiquity, bridging the gap between myth and reality by expanding our conception of the Amazon archetype to include the real female warriors of the ancient world